Kewenangan MUI Pasca Terbitnya PP No. 31 Tahun 2019 Tentang Peraturan Pelaksanaan UU No. 33 Tahun 2014 Tentang Jaminan Produk Halal - Elfirda Ade Putri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2021)
Halal certification is a written fatwa of the MUI which states the halalness of a product in accordance with Islamic law. This halal certificate is a requirement to include a halal label so that a product is suitable for consumption by Muslim consumers. Business actors must meet certain requirements and go through a series of processes that have been determined by the MUI to obtain a halal certificate. After obtaining a halal certificate, business actors obtain a halal label from the MUI to then be included on the product label. This halal certificate is only valid for a certain period of time and business actors must extend it to obtain halal certification for their products again. Whereas the problem arises when Law Number 8 of 1999 concerning Consumer Protection does not make halal certification and labeling a mandatory form for business actors, but is voluntary. Therefore, it can be said that halal certification and halal labeling do not have strong legal legitimacy, so they do not provide legal protection and certainty for halal food products for consumers.